BIRD STRIKE RISK ANALYSIS AT YOGYAKARTA INTERNATIONAL AIRPORT - Nursani, Ima
YIA Airport is a recently operational airport located in an area that has a natural habitat that is very crowded with wildlife, especially birds. This interaction between aircraft and wildlife can lead to various problems, such as bird strikes, disturbance to wildlife, changes in migratory behavior, and threats to the sustainability of certain species populations. Therefore, wildlife management and aviation operations are complex and important issues to address. In conducting a risk assessment, two methods are used, namely a method based on the Sowden method where the assessment is based on the size of the bird's body weight and flocking characteristics or social traits. The second method is the modified method, which in addition to considering the weight of the bird also considers the location, flight altitude and number of individual birds at the time of observation. Based on the combined results of the analysis of these methods, the following conclusions were obtained: 1 bird species categorized as high (Level 2) in the Sowden approach, also categorized as very high by the modified method, but there is 1 bird species categorized as low (level 5) in the Sowden approach, but in the modified method categorized as very high, this is due to the large number of these species observed and recorded in the airport area. In addition, several bird species in the Sowden approach are categorized as low level (5) but in the modified approach are categorized as having medium and high-risk levels, because in general these bird species are small but numerous and often move around the aircraft maneuvering area or airside. The results of the risk assessment analysis of the presence of birds in the YIA Airport area can be used to improve and refine the bird strike handling system to comply with applicable regulations.